Underutilization of the recommended frequency of focused antenatal care services in Northwest Ethiopia: Using Andersen's healthcare service utilization model approach - Asenake Abebaw Tareke; Yohannes Moges Mittiku; Animut Tagele Tamiru; Bayew Kelkay Rade; Temesgen Worku Gudayu (Elsevier, 2021)
Background: World Health organizations (2001) introduced an antenatal care model called Focused Antenatal Care (FANC) and recommended to have a minimum of four visits. This model is still feasible for low resource setting countries like Ethiopia. Underutilization of the recommended frequency of FANC results to hurt maternal and child health outcomes. Methods: Institutional based cross-sectional study was conducted from August 1 to October 30, 2019, at Debre Markos Referral Hospital, and a total of 358 post-partum mothers were participated in this study. A multivariable binary logistic regression was employed to identify factors associated with underutilization of the recommended frequency of FANC visits. A p-value < 0.05 was a cut-off point to declare statistical significance. Results: The magnitude of the recommended frequency of FANC visits was 55.6%. The high odds of underutilization were observed among mothers who did not watch television [AOR = 3.5; 95% CI (1.25-5.99)], not listing radio [AOR = 4.29; 95% CI (1.67-10.97)], reside far from health facility [AOR = 11.3; 95% CI (4.15-30.90)], and lack companionship/s when visited health facility [AOR = 3.5; 95% CI (1.91-6.50)]. Whereas, mothers age between 20 and 34 years [ AOR = 0.21; 95% CI (0.07-0.67)] and had follow up at private clinic/s [AOR = 0.013; 95% CI (0.001-0.143)] were inversely associated with underutilization. Conclusion: More than half of the total study participants were underutilized the recommended frequency of FANC which was high. Community mobilization through mass media, improve geographical access to the health facility, and improve client-provider relationships could improve FANC utilization.